Transfusion-related acute lung injury: a clinical review - Vlaar, Alexander PJ; Juffermans, Nicole P (The Lancet (British edition), 2013)
Three decades ago, transfusion-related acute lung injury (TRALI) was considered a rare complication of transfusion medicine. Nowadays, the US Food and Drug Administration acknowledge the syndrome as the leading cause of transfusion-related mortality. Understanding of the pathogenesis of TRALI has resulted in the design of preventive strategies from a blood-bank perspective. A major breakthrough in efforts to reduce the incidence of TRALI has been to exclude female donors of products with high plasma volume, resulting in a decrease of roughly two-thirds in incidence. However, this strategy has not completely eradicated the complication. In the past few years, research has identified patient-related risk factors for the onset of TRALI, which have empowered physicians to take an individualised approach to patients who need transfusion.